UJI PROVENANCE BENIH ULIN (Eusideroxylon zwageri Teijsm & Binn) DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS KINTAP KABUPATEN TANAH LAUT, KALIMANTAN SELATAN - Taufik Riadi; Gusti Muhammad Hatta; Basir Achmad (Universitas Lambung Mangkurat, 2020)
Ulin is a type of woody trees with a slow growth process that can be caused by two factors, namely internal factors (seed sources) and environmental factors (growth sites). Therefore the ulins from two different places (Kalsel and Kaltim) were tested in order to compare their growth. This was done by observing the growth of height and diameter of the stem. The method used was a quantitative method using the Independent-Sample T Test in the Staistical Package for Social Sciences to compare the growth of the two ulins. The results obtained at an average plant height showed that ulin Kaltim had better growth of 3.07 m than that of South Kalimantan which was 2.15 m. Furthermore, the diameter of ulin derived from Kaltim was 13.12 mm while that of South Kalimantan was 9.63 mm.Keywords: Ulin; Growth; Kaltim; Kalsel